Pemberdayaan Masyarakat untuk Meningkatkan Pemahaman Kerukunan Umat Beragama di Dusun Pondok, Desa Mojopuro - Putri, Dinda Fadia; Halimatussadiyah, Halimatussadiyah; Zahrah, Aulia; Solihin, Muhtar Mochamad (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was conducted in Mojopuro Village with the aim of increasing public understanding and awareness of the importance of interfaith harmony. The background to this activity was the potential for social friction due to a lack of interfaith understanding within the community. Pondok Hamlet, Mojopuro Village. The implementation method included outreach through print media, seminars and discussions, and counseling involving religious leaders, community leaders, and the Mojopuro Village community, particularly Pondok Hamlet. Evaluation was conducted through observation and interviews before and after the activity to measure improvements in community understanding. The results of the activity showed a significant increase in tolerance and communication between residents of different faiths. This service emphasizes the importance of community-based multicultural education as an effort to build sustainable social harmony at the village level.